Biofilm Extracellular Matrix - de Carvalho, Monica Moreno [UNESP]; de Oliveira, Vitória Parmejane [UNESP]; Okamoto, Ana Cláudia [UNESP]; Sonoda, Celso Koogi [UNESP]; Takamiya, Aline Satie [UNESP] (Taylor & Francis, 2025)
The extracellular matrix is essential for biofilm formation and makes possible a lifestyle as a community different from the planktonic state. The extracellular matrix is an important component of microbial biofilms, maintaining the spatial arrangement of cells and coordinating cellular functions throughout the structure. The extracellular polymeric substances that constitute the matrix include carbohydrates, proteins, nucleic acids, lipids, and other macromolecules, which are often organized into macromolecular complexes and/or associated with the surfaces of microbial cells within biofilms. Biofilm coordination occurs through the intercellular communication mechanism called quorum sensing, in which signaling molecules are excreted into the extracellular environment and accumulate as population density increases. In this chapter, we provide an overview of the biofilm extracellular matrix, its composition, function, and quorum-sensing cell–cell communication mechanism.